Bandgap-dependent onset behavior of output characteristics in line-tunneling field-effect transistors - Chun-Hsing Shih (2023)
The onset behavior of output characteristics in tunnel field-effect transistors (TFETs) importantly determines the performance of digital TFET-based circuits. In this paper, we analytically and numerically examine the dependence of the onset behavior of output characteristics on the bandgap of semiconductors in line-tunneling TFETs. The qualitative and quantitative analyses show that the output onset behavior in line-tunneling TFETs strongly depends on the bandgap because the roles of two factors, including the incident electron number and tunneling probability, in determining the variation of tunneling current under increasing drain voltage change oppositely when varying the bandgap. Particularly, the superlinear onset in line-tunneling TFETs can be effectively suppressed to reduce the saturation drain voltage by using low-bandgap semiconductors. Together with the advantages in on-current and subthreshold swing as shown previously, the significant superiority in output characteristic makes the use of low-bandgap materials to be an efficient approach for simultaneously enhancing the device and circuit performances of advanced line-tunneling TFETs.